2003
DOI: 10.1080/0954026021000045930
|View full text |Cite
|
Sign up to set email alerts
|

Substance misuse and psychiatric comorbidity: an overview of the OPCS National Psychiatric Morbidity Survey

Abstract: There have been a number of national surveys of psychiatric morbidity, which have included questions on drugs, alcohol, and tobacco. These surveys have helped delineate the overlap between substance use and dependence and other psychological morbidity. There is a strong association reported between high substance consumption and other measures of psychological problems. This article provides an overview of a national household survey, a survey of institutional residents with psychiatric disorders, and a nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 0 publications
3
69
1
4
Order By: Relevance
“…However, other studies have concluded the opposite: substance abuse is associated with worse mental health, following epidemiological or clinical diagnostic criteria (Cuijpers, Smit, Have, & de Graaf, 2007;Farrell et al, 2003;Martínez-Ortega, Jurado, Martínez-González, & Gurpegui, 2006;Regier et al, 1990). However, an important difference between those studies and the present one is that the mental health was self-rated by the prisoners in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…However, other studies have concluded the opposite: substance abuse is associated with worse mental health, following epidemiological or clinical diagnostic criteria (Cuijpers, Smit, Have, & de Graaf, 2007;Farrell et al, 2003;Martínez-Ortega, Jurado, Martínez-González, & Gurpegui, 2006;Regier et al, 1990). However, an important difference between those studies and the present one is that the mental health was self-rated by the prisoners in the current study.…”
Section: Discussioncontrasting
confidence: 73%
“…3,7,[40][41][42] Although our study provides valuable information on these binding sites in psychiatric pathology, additional studies examining binding specifically to membranous mGluR2/3 and mGluR5 and the affinity of novel mGluR2/3-and mGluR5-targeting drugs for these receptors in psychiatric disorders will provide valuable insight into the effectiveness of these drugs in the patient. 33 One confound of postmortem studies in neuropsychiatric disorders, is the presence of comorbid substance abuse, especially alcohol and drug abuse, or at least substantially higher alcohol 43 and illicit drug 44 intake in patients with psychiatric disorders. While reliable quantitative patient histories were not available in the present study, mGluR1/5 densities in the prefrontal cortex may be affected by alcohol, 45 and mGluR2 gene expression was reported to be reduced in the ACC of patients with alcohol addiction.…”
Section: Limitationsmentioning
confidence: 99%
“…Since then, numerous surveys have assessed the epidemiology of comorbidity internationally. [5][6][7][8][9][10][11][12][13][14][15][16][17] Several common themes have emerged from this work. First, relative to those without SUDs, people with SUDs have elevated rates of co-occurring Axis I and II disorders, and vice versa.…”
mentioning
confidence: 99%